A Comprehensive Survey on Exploring Covert Timing Channels in Network Security - Revathi, S.; kumar, B. Praveen; Ranjith, M.; Sachithanantham, M. (Journal of ISMAC, 2024)
Covert timing channels play pivotal roles in spying, hacking, and data theft, enabling secret communication and surreptitious data exchange. They also find utility in secure conversations, message concealment, security testing, and privacy protection, underscoring their versatile application across diverse domains. However, the accuracy of covert timing channels may be compromised by network traffic patterns and time delays, potentially affecting data integrity. This survey paper primarily provides an brief overview of identifying and mitigating these influencing factors of existing covert timing channels and presents a suggested system that integrates Reversible Covert Timing Channel (CTC) steganography and Elliptic Curve Cryptography (ECC) to ensure secure communication and data encryption. By leveraging this combination, the system aims to enhance the resilience of covert communication channels against adversarial interference while safeguarding the confidentiality and integrity of transmitted data.